The Utilization of Artificial Intelligence (AI) as an Assistive Tool for Civics Teachers in Designing Pancasila Character-Based Assessment - Sunandi, Isep; Suryono (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study investigates the use of Artificial Intelligence (AI) as an aid for PPKn (Pancasila and Citizenship Education) teachers in designing Pancasila character-based assessments. Using a sequential explanatory mixed-methods design, this study involved 45 PPKn teachers from public junior high and senior high schools in the city of Bandung as participants. Quantitative data were collected thru a structured questionnaire developed from the adaptation of the Technology Acceptance Model (TAM) and the TPACK framework, while qualitative data were obtained thru in-depth interviews with 12 informants selected thru purposive sampling. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and multiple regression, while qualitative data were analyzed thru six-phase thematic analysis. The results show that 82.2% of teachers using AI tools (ChatGPT, Gemini, and Microsoft Copilot) experienced a statistically significant improvement in the quality of character assessment instruments across all measured dimensions, with the most notable improvements in the completeness of rubric descriptors and alignment with Pancasila values. The efficiency of assessment design increased on average by 63.4% in terms of time saved. Multiple regression analysis reveals that teachers' digital competence is the strongest predictor of the quality of AI-assisted assessments, emphasizing that AI functions as a collaborative tool rather than an autonomous substitute for professional assessments